Limbo Atmosphere: The Experiences of Iranian Nurses of Disruptive Behaviors in Operating Room - Sahar Mirzaei; Marzieh Pazokian; Foroozan Atashzadeh- Shoorideh; Seyed Amir Hosein Pishgooie (Mashhad University of Medical Sciences, 2024)
Background: Operating room nurses are exposed to disruptive behaviors in different situations in operating room that affect them and their performance.Aim: The present study was performed with aim to explore the experiences of Iranian operating room nurses regarding disruptive behaviors in operating room settings.Method: This descriptive qualitative study was conducted in different university hospitals of Tehran. The data were collected by deep semi-structured interviews with 17 operating room nurses who were purposefully selected. Finally, the data were analyzed by the conventional content analysis approach.Results: In this study, four categories were extracted, including "activity in a poisonous atmosphere", "role negligence", "escape to a safety margin for adaptation", and "Indirect confrontation". The theme was "struggle in a limbo atmosphere caused by disruptive behaviors".Implications for Practice: Considering to the effect of disruptive behavior, it seems necessary to take training measures for improving "team-working" in operation room settings. Nursing managers can use the results of this research to determine patient care policies in the operating room in order to promote patient safety and improve the quality of care. It also seems necessary to design and implement a training program to evaluate its effect on changing disruptive behaviors.